1998
DOI: 10.1038/sj.onc.1201626
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic potential of a mutant human thyrotropin receptor expressed in FRTL-5 cells

Abstract: An abnormal stimulation of the cAMP pathway has been recognized as the primary event in various pathological situations that lead to goitrogenesis or thyroid tumors. Thyroid adenomas are monoclonal neoplasms that become independent of thyroid stimulating hormone (TSH) in their secretory function and growth. Mutated forms of the TSH receptor (TSHR) and the adenylyl cyclase-activating Gsa protein, which confer a constitutive activity on these proteins, have been observed in human adenomas. The FRTL-5 rat thyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…The development of hyperfunctioning adenomas in transgenic mice has also been observed after expression of a G as mutated transgene (Michiels et al, 1994). On the contrary, until now there has been no report of the induction of a fully neoplastic transformed phenotype in vivo or in vitro by either a mutationally activated G as or by a TSHR wild type genes (Fourne s et al, 1998;Russo et al, 1995a;SaõÈ d et al, 1994).…”
Section: Discussionmentioning
confidence: 96%
“…The development of hyperfunctioning adenomas in transgenic mice has also been observed after expression of a G as mutated transgene (Michiels et al, 1994). On the contrary, until now there has been no report of the induction of a fully neoplastic transformed phenotype in vivo or in vitro by either a mutationally activated G as or by a TSHR wild type genes (Fourne s et al, 1998;Russo et al, 1995a;SaõÈ d et al, 1994).…”
Section: Discussionmentioning
confidence: 96%
“…Similar TSH-independent stimulation of cAMP and proliferation have been reported separately both for GSP (Muca and Vallar, 1994) and a range of TSHR mutants (Porcellini et al, 1997) but few functional parameters were examined. The only previous study to attempt a direct comparison between GSP and TSHR clones obtained from the same parent population (Fournes et al, 1998) concluded that GSP exerted a weaker e ect than mTSHR (M453T) in terms of cAMP stimulation and doubling time in monolayer. However the former result was obtained in the presence of IBMX, and the latter may have been in¯uenced by the method of clonal selection (TSH-independent proliferation rather than`neutral' selection in G418).…”
Section: Activated Gsp and Tshr Both Confer Tsh-independent Growth Anmentioning
confidence: 99%
“…Intriguingly though, di erential sensitivity of ligand-dependent and -independent stimulation to downregulatory control could provide an explanation for the observation (Fournes et al, 1998) that anchorage-independent opposed to monolayer growth of FRTL5 was strikingly stimulated by mTSHR, but not by TSHstimulation of the wt receptor (nor by GSP).…”
Section: Constitutive Tshr Activity Provides a Signal Not Mimicked Bymentioning
confidence: 99%
See 2 more Smart Citations